2015
DOI: 10.1186/s12888-015-0648-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, associated factors and predictors of anxiety: a community survey in Selangor, Malaysia

Abstract: BackgroundAnxiety is the most common mental health disorders in the general population. This study aimed to determine the prevalence of anxiety, its associated factors and the predictors of anxiety among adults in the community of Selangor, Malaysia.MethodsA cross sectional study was carried out in three districts in Selangor, Malaysia. The inclusion criteria of this study were Malaysian citizens, adults aged 18 years and above, and living in the selected living quarters based on the list provided by the Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 56 publications
3
39
6
2
Order By: Relevance
“…In 2008, Scott et al found that having no qualifications was associated with anxiety in an obese group 23 . However, this finding was contrary to the Kader et al study, which found that a lower education level was not significantly associated with anxiety 24 . In our study, we found that every BMI unit increase was equal to1.1 times the odds of having anxiety in the obese patients with medical illnesses.…”
Section: Discussioncontrasting
confidence: 93%
“…In 2008, Scott et al found that having no qualifications was associated with anxiety in an obese group 23 . However, this finding was contrary to the Kader et al study, which found that a lower education level was not significantly associated with anxiety 24 . In our study, we found that every BMI unit increase was equal to1.1 times the odds of having anxiety in the obese patients with medical illnesses.…”
Section: Discussioncontrasting
confidence: 93%
“…Besides, the use of some self-designed questionnaire, the survey also included well-validated scales usually used for community surveys such as GAD-7, PHQ-9, PSS, and WEMWBS (for well-being). [ 19 20 21 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation (WHO) defines IPV as ‘behaviour within an intimate relationship that causes physical, sexual or psychological harm, including acts of physical aggression, sexual coercion, psychological abuse and controlling behaviours’ [ 5 ]. Women who experience IPV have a heightened risk of severe mental disorders, including depression [ 6 ], anxiety [ 7 ], and post-traumatic stress disorder [ 8 ]. The absence of good mental health can significantly undermine the ability for women to respond to IPV by feeding a cycle of violence and disempowerment [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%